Burnout during Electronic Medical Record Migration among Healthcare Providers: A Cross-Sectional Study at Mitra Paramedika Hospital, Indonesia - Dwi Raharjo, Untoro; Widianingrum , Bina; Riyadi, Sujono; Aninda, Ida; Nurdiyansyah , Andi Karisma; Asgiani , Piping (Journal of health research and technology, 2024)
Health Care Professionals (HCPs) are professionals who provide comprehensive care to patients, including medical documentation. During the migration from manual medical records to electronic medical records (EMR), the documentation process can pose additional challenges and induce stress, as HCPs must adapt to a new documentation process and face the risk of errors in documentation. This situation can lead to burnout related to the migration of medical records. This study aimed to identify the factors influencing burnout among HCPs during the migration of medical records at Mitra Paramedika Hospital. A correlational study was conducted involving 67 HCPs in the outpatient unit of Mitra Paramedika Hospital. Burnout data were collected through the distribution of a modified Maslach Burnout Inventory (MBI) questionnaire, and statistical analysis was performed using SPSS version 25 with the Cramer's V & Somer’s D statistical test. The evaluation revealed that the average burnout score among HCPs related to the migration of medical records was 1.86, categorizing it as moderate burnout. Factors such as respondents' age, gender, marital status, years of service, and profession had no significant impact on burnout among HCPs in the outpatient unit of Mitra Paramedika Hospital. Only educational status that significantly correlated to burnout in our study. Further assessment is required to explore another factors of burnout among HCPs during EMR migration.